Induction of Systemic Resistance in Maize and Antibiofilm Activity of Surfactin From Bacillus velezensis MS20 - Ali, Shireen Adeeb Mujtaba; Sayyed, R. Z.; Mir, Mohammad I.; Khan, M. Y.; Hameeda, Bee; Alkhanani, Mustfa F.; Haque, Shafiul; Mohammad Al Tawaha, Abdel Rahman; Poczai, Péter (Frontiers in Microbiology, 2022)
Surfactin lipopeptide is an eco-friendly microbially synthesized bioproduct that holds commendable potential in therapeutics as well as in agriculture and can be considered apt as an antibiofilm and anti-fungal bioactive agent. In the present study, production of surfactin by a marine strain Bacillus velezensis MS20 was carried out followed by physico-chemical characterization, anti-biofilm activity, plant groweighth promotion and quantitative Reverse Transcriptase – Polymerase Chain Reaction (q RT-PCR) studies were performed. From the results it was inferred that MS20 was found to produce biosurfactant (3300 mg L -1) under optimised conditions. From the physicochemical characterization (Thin layer chromatography (TLC), Fourier Transform Infrared (FTIR) Spectroscopy, Liquid Chromatography/ Mass Spectroscopy (LC/MS) and Polymerase Chain Reaction (PCR) amplification) it was revealed to be surfactin. From, bio-assay and scanning electron microscope (SEM) images, it was observed that surfactin (MIC 50 μg ml-1) has appreciable bacterial aggregation against clinical pathogens Pseudomonas aeruginosa MTCC424, Escherichia coli MTCC43, Klebsiella pneumoniae MTCC9751 and Methicillin resistant Staphylococcus aureus (MRSA) and showed fungal mycelial condensation property against a phytopathogen Rhizoctonia solani, Besides this q-RTPCR studies revealed 8-fold upregulation (9.34 ± 0.11 – fold) of srfA-A gene compared to controls. Further, treatment of maize crop (infected with R. solani) with surfactin and MS20 lead to the production of defense enzymes. In conclusion, concentration and synergy of carbon source with inorganic salts can ameliorate surfactin yield and application wise it has antibiofilm and antifungal activities in addition it’s induced systemic resistance in maize crop makes it good candidate to be employed in sustainable agricultural practices.